Diversity-oriented synthesis and cytotoxic activity evaluation of biaryl-containing macrocycles. Issue 11 (3rd March 2017) - Pérez-Labrada, Karell; Cruz-Mendoza, Marco A.; Chávez-Riveros, Alejandra; Hernández-Vázquez, Eduardo; Torroba, Tomás; Miranda, Luis D.
Abstract : Synthesis of biaryl-containing macrocycles has been carried out through a four-step approach comprising two Ugi four component reactions and a Suzuki–Miyaura macrocyclization. Abstract : Synthesis of biaryl-containing macrocycles has been carried out through a four-step approach comprising two Ugi four component reactions and a Suzuki–Miyaura macrocyclization. This protocol allowed the synthesis of 12- and 14-membered macrocycles. Cytotoxic activity evaluation showed that some of the molecules were effective against leukemia, glioblastoma and lung cancer cell lines (IC50 = 4.0, 5.9 and 7.6, respectively).